1996
DOI: 10.1007/bf02447513
|View full text |Cite
|
Sign up to set email alerts
|

Landscape influences on stream biotic integrity assessed at multiple spatial scales

Abstract: The biological integrity of stream ecosystems depends critically on human activities that affect land use/cover along stream margins and possibly throughout the catchment. We evaluated stream condition using an Index of Biotic Integrity (IBI) and a habitat index (HI), and compared these measures to landscape and riparian conditions assessed at different spatial scales in a largely agricultural Midwestern watershed. Our goal was to determine whether land use/cover was an effective predictor of stream integrity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
520
6
15

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 671 publications
(570 citation statements)
references
References 30 publications
29
520
6
15
Order By: Relevance
“…As basin 1 was different both in terms of distance and drainage direction, and there was no replicates for these differences, it was not possible also to analyze the relative effects of distance and drainage direction on composition, and to assess what of these factors would be responsible for the greater differentiation of the basin 1. Fish distribution is usually related to climatic, geomorphological, and historical factors (Roth et al, 1996;Poff and Allan, 1995). According to Hoeinghaus et al (2007), historical processes, such as speciation and dispersal, strongly affect local communities.…”
Section: Discussionmentioning
confidence: 99%
“…As basin 1 was different both in terms of distance and drainage direction, and there was no replicates for these differences, it was not possible also to analyze the relative effects of distance and drainage direction on composition, and to assess what of these factors would be responsible for the greater differentiation of the basin 1. Fish distribution is usually related to climatic, geomorphological, and historical factors (Roth et al, 1996;Poff and Allan, 1995). According to Hoeinghaus et al (2007), historical processes, such as speciation and dispersal, strongly affect local communities.…”
Section: Discussionmentioning
confidence: 99%
“…Upper and lower confidence levels (95%) are depicted in dashed lines. Data are based on studies by Roth et al, 1996;Harding et al, 1998;Marchetti and Moyle, 2001;Joy and Death, 2004;and Schweizer and Matlack, 2005. Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the line of the EPT overlays the upper confidence level of the combined macroinvertebrate, fish and EPT regression line. Data are based on studies by Roth et al, 1996;Harding et al, 1998;Euliss and Mushet, 1999;Hall et al, 2001;Marchetti and Moyle, 2001;Sponseller et al, 2001;Bojsen and Jacobsen, 2003;Collier and Quinn, 2003;Harding, 2003;Joy and Death, 2004;Bruns, 2005;and Schweizer and Matlack, 2005. …”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated negative relationships between biological indices and the percentage of agricultural land in the catchment or gradients of agricultural intensity (Roth, Allan & Erickson, 1996;Walser & Bart, 1999;Cuffney et al, 2000). These impacts are dependent on the different categories of production: many authors designate intensive agriculture as a cause of degradation in stream habitats (Allan & Johnson, 1997;Allan, 2004).…”
Section: Hierarchy Of Impacts: Urbanization Vs Agriculturementioning
confidence: 99%